PENGARUH ETOS KERJA, KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. THAMRIN BROTHER’S YAMAHA CENTRAL BENGKULU - Hermawati, Hermawati; Syofian, Syofian (Universitas Prof. Dr. Hazairin SH, 2022)
This research to determine how much influence work ethic, competence and job satisfactionhave on the performance of employees of PT. Thamrin Brother's Yamaha Central Bengkulu,and also to determine the relationship between the independent variables and the dependentvariable.The data analysis method uses multiple linear regression analysis, correlationanalysis, coefficient of determination, hypothesis testing F and t with work ethic (X1),Competence (X2) and Job Satisfaction (X3) as independent variables and employeeperformance as the dependent variable.The research method taken is quantitative by using asurvey method.The population in this study amounted to 75 employees at PT. ThamrinBrother's Yamaha Central Bengkulu.The sampling technique used was the saturatedtechnique.Sources of data obtained through library research and field studies in the form ofinterviews, observations and questionnaires. The results showed that work ethic (X1) andcompetence (X2) had a negative effect on employee performance (Y), and job satisfaction(X3) had a positive effect on employee performance (Y). But simultaneously X1, X2, and X3have an effect on Y.